TINGKAT PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN DIET HIPERTENSI - Emaus Zulkarnain, Albert; Pratama, Kharisma; Hartono (Literasi Intelektual, 2024)
Background: Hypertension is one of the most common and most prevalent cardiovascular diseases. Hypertension is known by the general public as